A Foucauldian interpretation of modern law : from sovereignty to normalisation and beyond - Martire, Jacopo (Edinburgh : Edinburgh University Press, 2018)
This text addresses a surprisingly overlooked Foucauldian conundrum: what is the logical relationship between modern law and power? Jacopo Martire investigates the development of modern law in conjunction with what Foucault termed biopolitical forms of power. He gives you a much-needed genealogical analysis of the modern legal phenomenon, opening new avenues for Foucauldian approaches to law.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 20, 2017).
Keywords: Foucault, Michel, -- 1926-1984.; Law; Law; Jurisprudence & general issues